PENGARUH LAYANAN KONSELING KELOMPOK DALAM MENGATASI PERILAKU AGRESIF SISWA MTsN MOJOSARI MOJOKERTO (Jurnal Bimbingan dan Konseling Islam, 2014)
This research examines the effect of group counseling services to cure the aggressive behavior of students in class VIII-H in MTsN MojosariMojokerto. It’s used quantitative research method with experimental research method, which to find the effect of a particular treatment over another in uncontrolled conditions. The researcher used a form of experiment one group pretest-posttest design, in this form there is a pretest before treated, the results of treatment can be known more accurately as it can be compared with the situation before being treated. And the results of this study states that the positive effect of group counseling services to lower the level of aggressiveness of class VIII-H MTsN Mojosari Mojokerto.